Design Thinking’s resources for in-situ co-design of mobile games - Challiol, Cecilia (2019)
Location-based Mobile Games have been growing in popularity in recent years. But these are widely explored only for outdoor spaces, since it has the advantage of using GPS data to obtain the user's current location. There is no unified solution to sense the user’s location in indoor spaces; so, games for these spaces are little explored. The design of Location-based Mobile Games, in many cases, requires the participation of multidisciplinary teams; so, they are co-designed by a group of people. However, there is no clear way of knowing how this codesign should be conducted. The aim of this paper is to propose a conceptual framework for in-situ co-design for indoor spaces on Location-based Mobile Games through the use of Design Thinking's resources. This conceptual framework could help facilitators with this kind of experience to consider what resources can be useful to this task. An experience of in-situ co-design of a Location-based Mobile Game for indoor spaces is presented using the proposed framework. In addition, a discussion is generated in relation to this kind of co-design.